2014
DOI: 10.4049/jimmunol.1400552
|View full text |Cite
|
Sign up to set email alerts
|

Collaboration between a Soluble C-Type Lectin and Calreticulin Facilitates White Spot Syndrome Virus Infection in Shrimp

Abstract: White spot syndrome virus (WSSV) mainly infects crustaceans through the digestive tract. Whether C-type lectins (CLs), which are important receptors for many viruses, participate in WSSV infection in the shrimp stomach remains unknown. In this study, we orally infected kuruma shrimp Marsupenaeus japonicus to model the natural transmission of WSSV and identified a CL (designated as M. japonicus stomach virus–associated CL [MjsvCL]) that was significantly induced by virus infection in the stomach. Knockdown of M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 82 publications
(37 citation statements)
references
References 52 publications
1
36
0
Order By: Relevance
“…Studies showed that WSSV virions could enter hemocytes; however, their genome replication and structural protein expression were unsuccessful in crayfish hemocytes [19]. The VP28 protein expression level was upregulated in the gills after WSSV challenge (Fig 1E), hematopoietic tissue cells [19] and stomach [18], but not in hemocytes after WSSV challenge in shrimp. All the results suggested that hemocytes had a mechanism to restrict WSSV replication.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Studies showed that WSSV virions could enter hemocytes; however, their genome replication and structural protein expression were unsuccessful in crayfish hemocytes [19]. The VP28 protein expression level was upregulated in the gills after WSSV challenge (Fig 1E), hematopoietic tissue cells [19] and stomach [18], but not in hemocytes after WSSV challenge in shrimp. All the results suggested that hemocytes had a mechanism to restrict WSSV replication.…”
Section: Discussionmentioning
confidence: 99%
“…The WSSV inoculum was acquired according to previous publications [18, 63]. Briefly, all tissues (except the hepatopancreas) of WSSV-infected shrimp were homogenized in sterile PBS (137 mM NaCl, 2.7 mM KCl, 2mM KH2PO4, 10 mM Na2HPO4, pH 7.4) at a ratio of 10% (w/v).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…mosGCTL-29 and mosGCTL-32 also significantly enhance Comamonas testosteroni, Chryseobacterium meningosepticum, and Serratia marcescens amplification (58). In addition to the ability of soluble CTLs to facilitate microorganism infection in mosquitoes, a previous study reported that a CTL of the kuruma shrimp Marsupenaeus japonicus (MjsvCL) facilitates white spot syndrome virus infection (59). CTLs are mainly in a soluble form in arthropods, and there are many types, indicating that they have important functions related to microbial infection.…”
Section: Fig 6 Anti-mosgctl-7 Serum Inhibits Jev Infection In Vivo Anmentioning
confidence: 99%